MIXED INITIATIVE AND ANTI-ISLANDING DETECTION METHOD AND SYSTEM - ZHANG, HUA; SASAN, MOSTAFAEI; WU, BIN; ZHANG, DONGLAI; SOOSAN, BEHESHTI (2014)
A mixed initiative and anti-islanding detection method and system. The method comprises the following steps: acquiring the change value ∆ω of the grid frequency in each control period, and acquiring the effect of the change value ∆ω of the grid frequency on the reactive power reference value Q ref by using a positive feedback frequency shift method and through gain processing, the correspondence between the change value ∆Q GCC of the reactive power reference value Q ref in each control period and ∆ω being as follows: ∆Q GCC = pf ∆ω, wherein K pf is the gain in the islanding effect pre-detection; when frequency shift occurs in the change value ∆ω of the grid frequency at 0.1Hz, determining that the islanding phenomenon probably occurs in an inverter, and triggering an initiative islanding detection method to perform further islanding detection; and otherwise, re-acquiring the change value ∆ω of the grid frequency, and performing gain processing on the ∆ω. In this method, only when the islanding effect is found